Evaluating filtration membranes and detection systems for use with virus surrogates - Stump, Emily D., author; Wickramasinghe, Sumith Ranil, advisor; Quackenbush, Sandra Lynn, committee member; Kipper, Matt, committee member; Pellegrino, John, committee member (Colorado State University. Libraries, 2010)
Virus filtration membranes are used to provide size exclusion removal of viruses during the purification of biopharmaceutical products. This viral clearance is required by regulatory agencies to ensure the safety of patients by preventing contamination of product by adventitious or endogenous virus. Viral clearance studies are often laborious, expensive, and require highly trained personnel. Detection and quantification of virus using standard assays has restrictions in terms of limit of detection, extraneous contamination and false positives. Moreover, biosafety for personnel and the environment is always a concern when working with live virus. In order to avoid the hazards of live, adventitious virus, bacteriophages have been used previously as virus surrogates (Aranha-Creado & Brandwein, 1999). While the health threat associated with using live viruses is eliminated using bacteriophages as surrogates, the detection systems and quantitative assays are still laborious and difficult. Development of a non-biological system to simulate and quantify virus particles could reduce the time taken to perform viral clearance tests; reduce development costs; reduce the risk to personnel performing the tests; and lead to more reliable data, since a non-biological system will reduce variability in assays. Here we develop a prototype of a novel, gigantic magnetoresistive (GMR) detection system for magnetic virus surrogates. In addition, we investigate various polymeric membranes for their ability to reject virus. Results will be used as a benchmark for evaluating the behavior of a future, superparamagnetic virus surrogate. GMR-based technology has increasingly been on the rise since the 2007 Nobel Prize in physics was awarded to Albert Fert and Peter Grünberg for its discovery. GMR sensors show potential for being extremely sensitive, inexpensive, and flexible devices for use in biodetection assays. Compared to the current magnetic detection technology of the superconducting quantum interference device (SQUID), which requires complex instrumentation and qualified users, GMR technologies can be fabricated in such a manner so as to be applied to lab-on-chip systems. Here we discuss the sensor design and fabrication. Initial measurements indicate that 104 iron oxide nanoparticles, approximately 20nm in diameter, can be detected in 0.5μl of solution. Various virus filters as well as ultrafiltration membranes were challenged with feed streams spiked with high concentrations of minute virus of mice (MVM) in the presence and absence of 1% bovine serum albumin (BSA) (w/v). Changes in permeate flux with filtrate volume were determined in conjunction with changes in rejection of parvovirus. Decrease in permeate flux resulting from fouling of BSA was evaluated for its effect on virus rejection. The results, which compare the performance of virus filtration and similar ultrafiltration membranes, provide insights into the comparison of live virus with future virus surrogates.
Department Head: Susan P. James.